Aliyah Madrasah Education Quality Management - Acep Saprulloh; Asep A. Fathurrohman; Marwan Setiawan (Journal of Islamicate Studies, 2021)
The background of this research is a phenomena of quality management in education at Madrasah Aliyah in Cimahi City, can’t be manage on planning, actuating and controlling.The core problem of this research are how to manage of quality management in education at Madrasah Aliyah begin from planning, actuating and controlling. The result of research find that quality management in education begin with make of vision and mision and then planning of database and madrasah profile for curricullum dan learning, madrasah administration, organization, equipment, fund of madrasah dan human resources also community participation and achievment of student. The finally proces of quality management in education is controlling from head of madrasah.